Front and back stage of tourism performance : imaginaries and bucket list venues - Riemer, Frances Julia (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Front and Back Stage of Tourism Performance situates our travel imaginaries, those dream destinations on our travel bucket lists, as co-constructed by the tourist industry, state development policies, and community negotiations, and as framed by modernity's new global cultural economy. As more people travel for pleasure than ever before, host communities and intermediaries are presented with tourism opportunities that all too often become flashpoints for local contestation and mechanisms for displacement. The ethnographically-grounded chapters describe tourist encounters shaped by geopolitics, complicated by war, and troubled by and enacted within the economic inequities of neocolonialism. The points of contact afford a unique vantage from which to view cultural identity, entrepreneurial strategizing, and natural resource management as global politics and relations of difference. They also illustrate the power of social networks, cultural display, and artistic performance as collective presentation, management apparatus, and structural critique. Drawing on a range of international case studies, this book will appeal to those interested in tourism, anthropology, global studies, environmental issues, microeconomics, and identity studies"--
Loose lips can sink tourism : true lies and secrecy and evasion during Nepal's Maoist insurgency / Sharon Hepburn -- From tourism to terrorism : Timbuktu and the traffic in global imaginaries / Angela M. Montague -- Staging culture for whom? : cultural performance and structural critique in highland Ecuador / Joe Quick -- Violence as tourist spectacle in eastern Indonesia : exploring the imaginaries of pain, identity and power in Manggaraian tourism encounters / Maribeth Erb -- Waah taj! : mediating Agra's heritage and local tourism economy / Riddhi Bhandari -- Seeing Fez / Jesse Dizard -- The Tulum Maya ruins : a place for foreigners / Maria Lauridsen Jensen -- Tropicality, purified spaces, and the colonial gaze : exclusionary policies in cruisetourism and its impact on the Caribbean / Matthew Nelson -- Economic security, community tension and tourist rankings on a small island in Mexico / Brandon Melecio Fischer and Todd Pierce -- Elephants are coming : safari, community, and Botswana's hunting ban / Frances Julia Riemer, Kgosietsile Velempini.
OCLC-licensed vendor bibliographic record.
Keywords: Tourism -- Anthropological aspects -- Case studies; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism